Clinical features of recurrent stroke after intracerebral hemorrhage - Taizen Nakase; Shotaroh Yoshioka; Masahiro Sasaki; Akifumi Suzuki (MDPI AG, 2012)
There have been many reports about the prognosis and risk factors of stroke recurrence following brain infarction (BI). However, little is known about the stroke recurrence after primary intracerebral hemorrhage (PICH). Therefore, we explored the recurrent stroke patients after initial PICH retrospectively, to reveal the critical factors of stroke recurrence. Acute BI (n=4013) and acute PICH patients (n=1067) admitted to the hospital between April 2000 and March 2009 were consecutively screened. PICH patients with a history of ICH and BI patients with a history of ICH were then classified into the ICH-ICH group (n=64, age 70.8±9.5 years) and ICH-BI group (n=52, age 72.8±9.7years), respectively. ICH lesions were categorized into ganglionic and lober types according to the brain magnetic resonance imaging. Subtypes of BI were classified into cardioembolism, large-artery atherosclerosis, small-artery occlusion and others. There was no difference in incidence of risk factors between ICH-ICH and ICH-BI groups. Distribution of initial PICH lesions was significantly abun- dant in the lobar type in the ICH-ICH group (P<0.01) and in ganglionic type in the ICH-BI group (P<0.02). Age of onset was significantly older in recurrent lobar ICH compared with recurrent ganglionic ICH (P<0.01: 73.6±10.0 and 59.1±9.0 years, respectively). In conclusion, ganglionic ICH patients may have a chance of recurrent stroke in both brain infarction and ganglionic ICH, suggesting the participation of atherosclerosis in intracranial arteries. Lobar ICH patients were older and prone to recurrent lobar ICH, suggesting the participation of cerebral amyloid angiopathy as a risk of stroke recurrence.